Formation of plasma electrons’ flows in the homogeneous beam-plasma system - Tanygina, D.M.; Anisimov, I.O.; Levitsky, S.M. (Вопросы атомной науки и техники, 2011)
1D simulation of the beam-plasma interaction demonstrates formation of quasi-periodical flows of background
plasma electrons. Flows directed along the electron beam velocity have larger velocities comparing with the flows
directed in the opposite side. This effect is associated with plasma electrons’ acceleration under the pressure of the
inhomogeneous HF electric field excited during the development of the beam-plasma instability. At the same time,
accelerated electrons moving parallel to the beam’s direction can interact with the excited Langmuir wave via
mechanism of Landau damping. Комп’ютерне моделювання пучково-плазмової взаємодії в одновимірній системі показало виникнення
квазіперіодичних потоків електронів фонової плазми. Потоки, направлені вздовж напрямку поширення
електронного пучка, мали більші швидкості у порівнянні із потоками, спрямованими в зворотному напрямкі.
Цей ефект пов’язаний із прискоренням плазмових електронів під дією високочастотного тиску неоднорідного
електричного поля, збудженого під час розвитку плазмово-пучкової нестійкості. При цьому прискорені
електрони, спрямовані паралельно до напряму руху пучка, взаємодіють із збудженою ленгмюрівською хвилею
за механізмом Ландау. Компьютерное моделирование пучково-плазменного взаимодействия в одномерной системе показало
возникновение квазипериодических потоков электронов фоновой плазмы. Потоки, направленные вдоль
распространения электронного пучка, имели большие скорости по сравнению с потоками, направленными в
противоположную сторону. Этот эффект связан с ускорением плазменных электронов под воздействием
высокочастотного давления неоднородного электрического поля, возбужденного во время развития пучково-плазменной неустойчивости. При этом ускоренные электроны, направленные параллельно пучку,
взаимодействуют с возбужденной ленгмюровской волной по механизму Ландау.